Implementasi Perancangan Sistem Informasi Berbasis Website di SD Negeri 18 Angge Palimbatan - Cania, Osi; Jehwae, Aminah (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
In today's digital era, the use of internet-based information media has become essential for every educational institution, including elementary schools. SD Negeri 18 Angge Palimbatan, as a formal educational institution, requires an effective platform to disseminate information to students, parents, teachers, and the wider community, as well as to improve the quality of school administrative services in a professional manner. This study aims to design and develop a web-based information system that serves as the primary medium for managing and delivering information within SD Negeri 18 Angge Palimbatan. The development method used is the Waterfall model, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The website was developed using the PHP programming language with the Laravel framework and MySQL as the database. The main features implemented include school profiles, student data, teacher information, news and announcements, activity galleries, and an admin panel for content management. The testing results show that the information system runs well, is responsive, and can be accessed from various devices. This website is expected to enhance transparency, communication efficiency, and the school's public image through digital media